Exploring how entrepreneurship education and entrepreneurial mindset shape students’ entrepreneurial intention in an Iranian university context - Saeid Karimi; Zahra Kosari Honarmand (PLoS ONE, 2026)
Despite the growing emphasis on entrepreneurship education, many university graduates continue to exhibit low entrepreneurial intention and engagement. Understanding how education and entrepreneurial mindset jointly influence this intention remains limited, particularly in non-Western contexts. Drawing on the Theory of Planned Behavior (TPB), this study investigates how entrepreneurship education and entrepreneurial mindset shape students’ entrepreneurial intention through the TPB constructs—attitude toward entrepreneurship, subjective norms, and perceived behavioral control (PBC). Using a self-administered survey, 190 valid responses from students at an Iranian public university were analyzed via structural equation modeling (SEM-PLS). The findings indicate that attitude and PBC significantly influence entrepreneurial intention, while subjective norms do not have a direct effect but exert an indirect influence through attitude and PBC. Entrepreneurship education positively affects PBC and indirectly influences entrepreneurial intention via PBC but does not directly predict intention, attitude, or subjective norms. Furthermore, entrepreneurial mindset significantly shapes attitude, subjective norms, and PBC, and indirectly influences entrepreneurial intention through these TPB components. Overall, the findings highlight the need for more experiential and practice-oriented educational approaches to ensure that improvements in entrepreneurial mindset and educational exposure translate into stronger entrepreneurial intention. Practical recommendations are offered to enhance the design and delivery of entrepreneurship education in higher education settings.